Pro: continuous positive airway pressure and cardiovascular prevention. Issue 5 (10th May 2018) - Martinez-Garcia, Miguel Angel; Campos-Rodriguez, Francisco; Javaheri, Shahrokh; Gozal, David
In the clinical realm, the highest degree of evidence driving practice guidelines originates from randomised controlled trials (RCTs) and meta-analysis of RCTs. For practice changes to occur, adequate RCT methodology and optimal sample size, as well as accurate definition of primary objectives and patient selection, are paramount, along with satisfactory adherence to the targeted intervention in a high proportion of the participants. Critically, the results of any of such trials can only apply to the targeted population and cannot be extrapolated to alternative groups, even if they suffer from the same disease [1]. Furthermore, if controversial findings emerge between previous basic and clinical studies, a cogent explanation for such discrepancies would be required to identify future study directions. The methodological limitations of the current RCTs on the CPAP effect on cardiovascular protection do not support a change in our clinical practice http://ow.ly/V11730ieGYk